Evaluation of hypobaric hypoxia as a low stress alternative to carbon dioxide euthanasia for use with nursery piglets - Buzzard, Brandi L. (Kansas State University, 2012)
Malnourished piglets that suffer from periweaning failure to thrive syndrome (PFTS) may show no signs of respiratory or enteric diseases but may have decreased feed intake and become debilitated after weaning. Euthanasia is a necessary component of swine production as it is sometimes the only option to alleviate suffering of piglets that are born with congenital defects or suffer from PFTS. Fifty-eight nursery-aged piglets were utilized in two experiments to evaluate blood parameter differences between healthy and unthrifty piglets and to compare euthanasia methods. Piglets were categorized into two health groups: healthy or unthrifty. During selection, blood was collected for analysis of blood parameters. Piglets were euthanized 24-32 hours after initial blood sampling and a second sample was collected for comparison. After euthanasia, piglets were necropsied for evaluation of euthanasia on pulmonary lesions. No significant difference in number of pulmonary lesions was found between health groups (P = 0.88). Healthy piglets had higher concentrations of glucose, ionized calcium and sodium, and greater pCO₂ than unthrifty piglets (P ≤ 0.05). Unthrifty piglets showed higher concentrations of hemoglobin and hematocrit (P = 0.0002) than healthy piglets. Piglets were assigned to one of two euthanasia methods to compare electrophysiological and behavioral parameters of hypobaric hypoxia and carbon dioxide gas. Two piglets at a time were euthanized for each method. One animal in the pair was fitted with electrocardiogram and electroencephalogram monitoring devices during euthanasia. Behavioral parameters were also recorded. The average treatment times were 27.4 ± 6.7 minutes for HH and 13.8 ± 5.1 minutes for CO2. Piglets euthanized via CO2 reached an isoelectric state faster than piglets euthanized via HH (P = 0.009). Behavioral observations revealed gasping in 100% of CO2 euthanized piglets during the first five minutes of treatment and only 28.6% of HH euthanized piglets during the same period. During HH, 57.1% of piglets became ataxic in the first five minutes while 76.9% of CO2¬ piglets became ataxic during the same period. Results of this trial indicate that HH may be a lower stress alternative to CO₂ as it causes fewer incidences of aversive behaviors in early stages of treatment.
Keywords: Stress; Swine; Euthanasia; Behavior; Hypobaric hypoxia; Pig; Animal Diseases (0476); Animal Sciences (0475)